Legal and Ethical Dimensions of Artificial Intelligence (AI) Utilization within Indonesia's Pluralistic Society - Amrizal Siagian; Suryanto Siyo (Journal of Law, Society and Living Norms, 2025)
Social interaction within society required norms and values that regulated relationships between individuals. One essential value supporting social order was moral responsibility. With rapid technological advancement, particularly artificial intelligence emergence, there was an urgent need for a balanced legal and ethical framework. This was especially important in Indonesia's diverse society, guided by Pancasila's foundational values. Digital technology development had significantly impacted law, social relations, economics, education, culture, and public administration. This study employed a qualitative approach through sociological empirical research, relying on social reality observation using logic and real-life experience rather than theoretical speculation. The findings indicated that artificial intelligence use in Indonesia had become increasingly widespread. However, this growth lacked a clear and comprehensive legal framework, contrasting with other countries that had begun formulating policies grounded in ethics and social justice for artificial intelligence governance. Given this situation, all stakeholders, including government, academia, and civil society needed to participate in formulating adaptive and flexible regulations rooted in legal principles, ethical considerations, and human rights. This approach ensured artificial intelligence application in Indonesia served as a tool for equitable, inclusive, and human-centered development, rather than becoming a source of legal uncertainty and social inequality.